Nanoskin (R) Subcutaneous Implant in Guinea Pigs - Kaminagakura, Kryscia Natsuaki [UNESP]; Sato, Silvana Sue [UNESP]; Sugino, Patricia [UNESP]; Santos, Daniela Carvalho [UNESP]; Kataki, Laryssa [UNESP]; Padovani, Carlos Roberto [UNESP]; Basmaji, Pierre [UNESP]; Schellini, Silvana A. [UNESP] (Lippincott Williams & Wilkins, 2018)
Purpose: To evaluate the suitability of Nanoskin((R)), a biomaterial derived from bacterial cellulose, as an alternate material for repairing the posterior lamellae of the eyelids. Methods: Forty guinea pigs received a fragment of Nanoskin((R)) subcutaneously in the dorsal region. The animals received Nanoskin((R)) (group 1) or Nanoskin((R)) coated with a gelatin layer (group 2). The animals were observed daily for over 7, 30, 90, or 180 days with the subcutaneous implants in place. The animals were euthanized at a designated time and the Nanoskin((R)) was removed for histologic, morphometric, and transmission electron microscopy evaluation. Results: The results were similar for both groups. The subcutaneously implanted Nanoskin((R)) resulted in good tissue integration, induced mild inflammation, and was surrounded by a delicate pseudocapsule. Conclusion: The good tissue integration of Nanoskin((R)) in study indicates that it may be a potential material for application as a substitute of posterior eyelid lamellar tissue. Further clinical studies are required to confirm the preliminary outcomes of this experimental study.